Pengembangan Media Pembelajaran TITANICS (Three-Dimensions Interactive Animation of Thermodynamics) Untuk Meningkatkan Hasil Belajar Kognitif Peserta Didik - Arrahmat, Mohamad Wahdiansyah; Anggaryani, Mita (Universitas Negeri Surabaya, 2025)
There is a lot of research related to the development of learning media that utilizes technological advances, one of which is 3D animation-based learning media. However, it is different from the TITANICS learning media. This is because the TITANICS learning media developed is able to train students' cognitive thinking levels from level C1 (remembering) to C4 (analyzing) by utilizing 3D animation in the form of a combination of video and interactive PPT (PowerPoint). This research focuses on analyzing the validity of the TITANICS learning media which has been developed using the ADDIE (Analyze, Design, Development, Implementation and Evaluation) development research model. Media validation is carried out by three validators who are expert lecturers in the field of learning media. Media validity is reviewed from four aspects, namely media appearance, language used, suitability and media operation. The research results showed that the validity scores obtained in these four aspects were 91.66%, 91.66%, 90.27% and 89.58%. Thus the average validation score percentage obtained for TITANICS learning media was 90.79% in the very valid category. So, it can be stated that the TITANICS learning media is suitable for use as a learning media to train students' cognitive thinking levels from level C1 (remembering) to C4 (analyzing) in learning physics on thermodynamics material. Keywords: Thermodynamics, Learning Media, 3D Animation